Cancer Cell Membrane Camouflaged Nanoprobe for Catalytic Ratiometric Photoacoustic Imaging of MicroRNA in Living Mice. Issue 12 (7th February 2019) - Zhang, Kai; Meng, Xiangdan; Yang, Zhou; Cao, Yu; Cheng, Yaru; Wang, Dongdong; Lu, Huiting; Shi, Zhuojie; Dong, Haifeng; Zhang, Xueji
Abstract: Herein, a cancer cell (MCF‐7 cell) membrane‐encapsulated dendritic mesoporous silica nanoparticle simultaneously functionalized with DNA‐photoacoustic (DNA‐PA) probes and glutathione (GSH)‐responsive DNA fuel strands for PA imaging of tumor‐related miRNA in living mice with signal amplification ability is developed. It is demonstrated that one target miRNA can trigger disassembly of multiple PA fluorophore probes from the quencher with the aid of GSH‐responsive DNA fuel strands via the entropy‐driven process, resulting remarkable amplified change of PA signal ratio. Using oncogenic miRNA‐21 as a model, a linear relationship between miRNA‐21 concentrations and PA ratio in a dynamic range from 10 × 10 −12 m to 100 × 10 −9 m and a limit of detection down to 11.69 × 10 −12 m are established. The accurate PA signal observation related to miRNA‐21s in the tumor area in living mice is demonstrated, and the PA signal ratio increases significantly via the injection of miRNA‐21. It is anticipated that the catalytic ratiometric PA imaging system can be applied to an array of molecular detection in living system by rational detection probe design. Abstract : Cancer cell (MCF‐7 cell)‐membrane‐encapsulated dendritic mesoporous silica nanoparticles (DMSNs) simultaneously functionalized with DNA‐photoacoustic (DNA‐PA) probes and glutathione‐responsive DNA fuel strands are developed for PA imaging of tumor‐related miRNA in living mice with a signal amplification ability. This catalytic ratiometric PA imaging system can be applied to the detection of an array of molecules in living systems by rational detection probe design.